PENGGUNAAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA SEKOLAH DASAR - Dea Rona Sapitri; Masrul; Muhammad Syahrul Rizal; Iis Aprinawati; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low descriptive writing skills of students in Indonesian language learning in class III SDM 014 Pulau Payung, Rumbio Jaya District, Kampar Regency. One solution to overcome this problem is to apply the Picture and Picture learning model. The purpose of this study is to improve descriptive writing skills in Indonesian language learning. The research method used by the researcher is Classroom Action Research (CAR), which is carried out in two cycles, each cycle consists of 2 meetings and 4 stages, namely planning, implementation, observation and reflection. The research time was carried out starting in October 2024. The subjects of this study were 20 class III students, consisting of 9 boys and 11 girls. Data collection techniques were in the form of documentation and observation. This was before the action was taken, the students' cooperation ability was 25%. After the action was taken in cycle I it increased to 60%. While in cycle II it increased to 90%. Thus it can be concluded that using the Picture and Picture learning model can improve the descriptive writing skills of class III SDM 014 Pulau Payung students.